2013
DOI: 10.1177/0894845313495590
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity of Career Decision-Making Profiles Over Time Among Chinese College Students

Abstract: Two studies were conducted to validate the Chinese version of the Career Decision-Making Profiles (CDMP) questionnaire, a multidimensional measure of the way individuals make career decisions. Results of Study 1 showed that after dropping 1 item from the original CDMP scale, the 11-factor structure was supported among Chinese college students (N = 334). Results of Study 2 (N = 372) replicated this factor structure and revealed that the CDMP accounted for 25% and 32% of the variances in participants' career dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…For example, the statement "I consider it important to choose an option that will satisfy my family and close friends" represents the Desire to please others dimension. The proposed model's internal structure and cross-cultural equivalence were supported in the Hebrew, English and Chinese versions of the CDMP questionnaire (Gati et al, 2010a(Gati et al, ,2010bTian et al, 2014). The internal-consistency, test-retest reliabilities, one year stability, concurrent validity, and incremental validity of the CDMP were also supported (Gadassi, Gati, & Wagman-Rolnick, 2013;Gati & Levin, 2012;.…”
Section: Instrumentsmentioning
confidence: 64%
“…For example, the statement "I consider it important to choose an option that will satisfy my family and close friends" represents the Desire to please others dimension. The proposed model's internal structure and cross-cultural equivalence were supported in the Hebrew, English and Chinese versions of the CDMP questionnaire (Gati et al, 2010a(Gati et al, ,2010bTian et al, 2014). The internal-consistency, test-retest reliabilities, one year stability, concurrent validity, and incremental validity of the CDMP were also supported (Gadassi, Gati, & Wagman-Rolnick, 2013;Gati & Levin, 2012;.…”
Section: Instrumentsmentioning
confidence: 64%
“…The American participants completed the English version of CDMP (Gati et al, 2010) and the Chinese participants completed the Chinese version (Tian et al, 2014). Since item 3 was excluded from the Chinese version of the CDMP in a previous validation study (Tian et al, 2014), to ensure the metric equivalence of this measure across cultures, item 3 was also dropped from the English version (cf., Cheung & Rensvold, 2002). Participants were asked to respond to the remaining 32 items representing the 11 CDMP dimensions (viz., two items representing the information gathering dimension and 3 items for each of the other ten dimensions), as well as an additional warm-up item and two validity items.…”
Section: Instrumentsmentioning
confidence: 99%
“…For example, it has been found that among American university students, scores on dependence on others (DO) and desire to please others (DP) were extremely low (e.g., Gati et al, 2010); however, the results obtained from Chinese university students showed that the scores on these two dimensions were relatively higher than those found among US students (Tian et al, 2014). To date, no comparative work has been done to examine the cultural variations of CDMP, along with the mechanisms underlying this process.…”
mentioning
confidence: 97%
“…Additionally, studies have translated, adapted, and tested the validity of the current assessment tools in additional cultures (CDMP; Tian et al, 2014;CDDQ;Creed & Yin, 2006;Mau, 2001) and compared the different patterns of responses among various cultures (CDMP; Guan et al, 2015;CDDQ;Mau, 2004 found that Asian-Americans had greater difficulties then Caucasian-Americans, in both highschool and college samples. Another study by Mau (2001) found that Taiwanese undergraduate students experienced more career decision-making difficulties than American students.…”
Section: Cultural Differences In Career Decision-makingmentioning
confidence: 99%